Turks and Caicos Islands : Financial Sector Assessment Program. (IMF Staff Country Reports; Country Report, 2015)
This paper discusses key findings and recommendations made in Financial System Stability Assessment for Turks and Caicos Islands. Although the financial oversight framework has significantly improved, the Financial Services Commission (FSC) should strive for further progress. Major advances have been made regarding the operational independence of the FSC and staffing. Nonetheless, the outdated Banking Ordinance and Insurance Ordinance need urgent overhaul. The functioning of the FSC should be strengthened by enhancing Board oversight, filling key positions at Board and senior management levels, strengthening communication and consultation with the industry, and improving the supervision and risk assessment capacities of FSC staff.